How decentralization drives a change of the institutional framework on the distribution grid level in the electricity sector: The case of local congestion markets - Marius Buchmann (Jacobs University Bremen, Bremen Energy Research (BER), 2019)
The increasing share of renewables in the electricity system results in congestion on all network levels. To address this congestion, the EU Commission proposed that distribution network operators become responsible for local congestion management. Within this paper we analyze the institutional implications of the introduction of local congestion markets and identify three discrimination concerns related to the DSO's role on these markets. We will argue that the standard governance models (legal unbundling, ownership unbundling, IDSO) are not adequate here. Instead, we discuss two novel approaches: The introduction of Independent Distribution Operators (IDO) or alternatively, a Common Flexibility Platform (CFP). Since the CFP does not require stronger unbundling of DSOs, we recommend to investigate this solution further.
Keywords: D47; L52; L 94; L97; L98; 330; local congestion market; congestion management; regulation; unbundling; discrimination